2020
DOI: 10.1186/s12876-020-01210-5
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic clip application for large pedunculated polyps before snare polypectomy may decrease immediate postpolypectomy bleeding

Abstract: Background: Although prophylactic clip application before polypectomy may prevent postpolypectomy bleeding (PPB), the usefulness of prophylactic clipping in the treatment of large pedunculated polyps is controversial in some prospective randomized studies. This study was conducted to evaluate the efficacy of prophylactic clip application and to investigate the predictors of PPB in large pedunculated colorectal polyps. Methods: A total of 137 pedunculated polyps (size ≥1 cm) in 116 patients were prospectively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Though The application of prophylactic clips could reduce the incidence of PPB [5,7], Douglas K [8] pointed out that multiple adverse events, including bleeding, thermal injury and positive resection margins, should be synchronously considered in pedunculated polyp polypectomy. The application of prophylactic clips may make the resection di cult to get close to the polyp base, thus leading to positive resection margins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though The application of prophylactic clips could reduce the incidence of PPB [5,7], Douglas K [8] pointed out that multiple adverse events, including bleeding, thermal injury and positive resection margins, should be synchronously considered in pedunculated polyp polypectomy. The application of prophylactic clips may make the resection di cult to get close to the polyp base, thus leading to positive resection margins.…”
Section: Discussionmentioning
confidence: 99%
“…The application of prophylactic clips before snare polypectomy has been shown to reduce PPB and immediate postpolypectomy bleeding (IPPB) for large pedunculated polyps [5][6][7]. However, the existence of endoclips hinders resection near the base of the stem, which might lead to a high risk of tumor remnants [8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the morphology of polyp is one of an important factor related to the complications of a colonoscopy resection of polyps [20]. Examples include Yamada type III polyps (those with short pedicles), regarding mucosal burns and perforation during resection; large polyps that contain large blood vessels in the pedicle that can cause bleeding after the endoscopic resection of colorectal polyps; and delayed bleeding [5,20]. Therefore, the pedicle of polyps needed to be evaluated in detail before colonoscopy for accurate evaluations of Yamada classi ed.…”
Section: Discussionmentioning
confidence: 99%
“…However, no clinical studies comparing DPPB between CSP with or without clip placement. Additionally, although some reports have found no DPPB after CSP, this event still occurs under real-world clinical conditions, and whether prophylactic placement of clips is effective for preventing DPPB remains controversial [15][16][17][18]. Furthermore, no reports have clari ed whether DPPB can be prevented by post-resection irrigation and inspection of the mucosal defect in the resection stump [19,20], or by checking for complete hemostasis after polypectomy, although both steps are considered effective.…”
Section: Backgroudmentioning
confidence: 99%